2019
DOI: 10.1111/trf.15630
|View full text |Cite
|
Sign up to set email alerts
|

Transcription‐mediated amplification blood donation screening for Babesia

Abstract: BACKGROUND Transfusion‐transmitted Babesia microti is well recognized in the Northeast and upper Midwestern United States. Blood donation screening in Babesia‐endemic states has occurred under investigational protocols prior to US Food and Drug Administration–licensed test availability. Here, we provide a prospective screening summary of nucleic acid testing (NAT) as part of a multicenter Babesia pivotal trial followed by extended investigational use. METHODS From June 2017 to February 2018, 176,928 donation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In addition, the incubation period for development of symptoms after transfusion is as long as six months [ 6 ]. Furthermore, donor surveillance studies and prospective screening have also identified parasitemic donations (i.e., positive nucleic acid test) throughout the year, although positive donations still tend to occur from June to October [ 33 ].…”
Section: Epidemiology: Geographic Distribution Seasonality and Transmissibilitymentioning
confidence: 99%
“…In addition, the incubation period for development of symptoms after transfusion is as long as six months [ 6 ]. Furthermore, donor surveillance studies and prospective screening have also identified parasitemic donations (i.e., positive nucleic acid test) throughout the year, although positive donations still tend to occur from June to October [ 33 ].…”
Section: Epidemiology: Geographic Distribution Seasonality and Transmissibilitymentioning
confidence: 99%
“…Not only are babesial piroplasmids transmitted by ticks, they are transmitted by blood transfusion [53], organ transplantation [54], and maternal-fetal transmission [55][56][57][58]. Similarly, Lyme disease spirochetes can be transmitted by maternal-fetal transmission [59][60][61][62][63].…”
Section: Human Babesiosis As a Tick-borne Zoonosismentioning
confidence: 99%
“…Limited epidemiological surveys in Babesia-endemic states using laboratory-based nucleic-acid-based tests (NAT) and antibody testing have provided important information about the percentage of asymptomatic infected donors, the relationship between seropositivity and parasitemia, and the seasonality of transmission in endemic areas (Leiby et al, 2005(Leiby et al, , 2014Johnson et al, 2009). In more recent years, results from prospective studies in large cohorts of blood donors conducted under the Investigational New Drug protocols have shed light on the prevalence of B. microti infections in asymptomatic healthy adults in endemic areas and non-endemic states (Levin et al, 2016;Moritz et al, 2016;Tonnetti et al, 2020). Results showed one confirmed infected sample per 1331 donations in endemic states (67 positives/89,153 donations) (Moritz et al, 2014) and one confirmed positive per 2351 donations (211 positives/496,270 donations) (Tonnetti et al, 2020) in endemic states plus Florida using investigational NAT assays.…”
Section: Persistent Infectionmentioning
confidence: 99%
“…In more recent years, results from prospective studies in large cohorts of blood donors conducted under the Investigational New Drug protocols have shed light on the prevalence of B. microti infections in asymptomatic healthy adults in endemic areas and non-endemic states (Levin et al, 2016;Moritz et al, 2016;Tonnetti et al, 2020). Results showed one confirmed infected sample per 1331 donations in endemic states (67 positives/89,153 donations) (Moritz et al, 2014) and one confirmed positive per 2351 donations (211 positives/496,270 donations) (Tonnetti et al, 2020) in endemic states plus Florida using investigational NAT assays. Cumulative results from the surveillance programs (Herwaldt et al, 2011;Linden et al, 2018;Gray and Herwaldt, 2019) and donor testing studies (Johnson et al, 2009;Moritz et al, 2016) have revealed that while tickborne infections are seasonal, transfusion transmitted cases occur year-round, although they too peak during the tick-transmission season.…”
Section: Persistent Infectionmentioning
confidence: 99%